2019
DOI: 10.1371/journal.pone.0227280
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ consultation counts and associated factors in Swiss primary care – A retrospective observational study

Abstract: BackgroundResearch on individual general practitioner (GP) workload, e.g. in terms of consultation counts, is scarce. Accurate measures are desirable because GPs’ consultation counts might be related to their work satisfaction and arguably, there is a limit to the number of consultations a GP can hold per day without jeopardizing quality of care. Moreover, understanding the association of consultation counts with GP characteristics is crucial given current trends in general practice, such as the increasing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In fact, the trend was similar in both DRG-groups for each age class, but the levels of costs and consultations depended on age. This is in line with other studies: [ 27 ] showed that an increase in the number of the elderly and infants, in the British population, led to a higher consultation rate of these 'extreme' age groups and [ 28 ] showed that, in Switzerland, an increase in consultation rates was associated with increasing age. In fact, the demand for primary care consultations is likely due to the accumulation of chronic conditions in the aging population [ 29 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the trend was similar in both DRG-groups for each age class, but the levels of costs and consultations depended on age. This is in line with other studies: [ 27 ] showed that an increase in the number of the elderly and infants, in the British population, led to a higher consultation rate of these 'extreme' age groups and [ 28 ] showed that, in Switzerland, an increase in consultation rates was associated with increasing age. In fact, the demand for primary care consultations is likely due to the accumulation of chronic conditions in the aging population [ 29 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…We performed all analyses using the statistical software package R (version 3.6.1) and considered p < 0.05 statistically significant for all tests [ 64 ]. For all analyses with specific GPs’ characteristics (e.g., age, gender, years in practice, consultations, type of practice), we used a validated dataset from 2018 [ 65 ] since differentiation between single and group GP practices is not yet possible in our database.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the patients participating to the present study presented slightly lower level education, but similar age and health status compared to the general practitioners' patients of other Swiss studies. [43][44][45] T-tests analysing physician gender differences in empathy measures showed that most empathy measures (4/6) did not significantly differ between female and male physicians (Table 3). Nevertheless, female physicians selfrated their empathic concern significantly above male physicians, and male physicians were significantly more vocally synchronised with their patient compared to female physicians.…”
Section: Resultsmentioning
confidence: 97%
“…The patients participating in the present study had a slightly lower level of education on average, but similar age and health status compared with the general practice patients of other Swiss studies. 40 42 …”
Section: Resultsmentioning
confidence: 99%